Effect of inorganic oxide supports on the activity of chromium‐based catalysts in ethylene trimerization. (21st June 2019) - Fallahi, Maryam; Ahmadi, Ebrahim; Mohamadnia, Zahra
Abstract : Novel heterogeneous catalysts were prepared using immobilization of bis(2‐decylsulfanylethyl)amine–CrCl3 (Cr‐SNS‐D) on various supports, namely commercial TiO2, Al2 O3 and magnetic Fe3 O4 @SiO2 nanoparticles, to yield solid catalysts denoted as support@Cr‐SNS‐D. The structure of the catalysts was confirmed on the basis of spectroscopic analyses, N2 adsorption–desorption and inductively coupled plasma (ICP) analysis. The surface areas of Al2 O3 @Cr‐SNS‐D, Fe3 O4 @SiO2 @Cr‐SNS‐D and TiO2 @Cr‐SNS‐D catalysts were determined to be 70, 23 and 41 m 2  g −1, respectively. A decrease in surface area from that of the supports clearly establishes accurate immobilization of Cr‐SNS‐D catalyst on the surface of the parent carriers. The loading of Cr was determined to be 0.02, 0.16 and 0.11 mmol g −1 for Cr‐SNS‐D supported on TiO2, Al2 O3 and Fe3 O4 @SiO2, respectively, using ICP analysis. After preparation and full characterization of the catalysts, ethylene trimerization reaction was accomplished in 40 ml of dry toluene, at 80°C and 25 bar ethylene pressure and in the presence of methylaluminoxane (Al/Cr = 700) within 30 min. The supported chromium catalysts were found to be efficient and selective for the ethylene trimerization reaction. The highest activity (74 650 g1‐hexene  gCr −1  h −1 ), as well as no polyethylene formation during reaction processes, was observed when TiO2 was used as the catalyst support. Abstract : Heterogeneous catalysts were prepared using immobilization of bis(2‐decylsulfanylethyl)amine.CrCl3 (Cr‐SNS‐D) on different supports such as commercial TiO2, Al2 O3, and magnetic Fe3 O4 @SiO2 nanoparticles to yield the solid catalysts denoted as support@Cr‐SNS‐D. Ethylene trimerization reaction was accomplished in 40 mL of dry toluene, 80 °C temperature, 25 bar ethylene pressure and in the presence of MAO (Al/Cr=700) within 30 minutes. The highest activity (74650 g 1‐Hexene/(g Cr×h)) as well as no polyethylene formation during reaction processes were observed if TiO2 was used as catalyst support.